Harry Potter and the philosopher's stone - Rowling, J. K. (Bloomsbury London, 2014)
When a letter arrives for unhappy but ordinary Harry Potter, a decade-old secret is revealed to him that apparently he's the last to know. His parents were wizards, killed by a Dark Lord's curse when Harry was just a baby, and which he somehow survived. Leaving his unsympathetic aunt and uncle for Hogwarts, a wizarding school brimming with ghosts and enchantments, Harry stumbles upon a sinister mystery when he finds a three-headed dog guarding a room on the third floor. Then he hears of a missing stone with astonishing powers which could be valuable, dangerous or both. An incredible adventure is about to begin!